Optical glass and optical element

The glass composition with controlled oxide contents achieves high refractive index, low dispersion, and low glass transition temperature, addressing the limitations of existing optical glasses for precision pressing and optical element manufacturing.

JP2025009783AActive Publication Date: 2025-01-20HOYA CORPORATION +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2024036601
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-06-28
Filing Date
2024-03-11
Publication Date
2025-01-20
Estimated Expiration
2044-03-11

AI Technical Summary

Technical Problem

Existing optical glasses lack a balance of high refractive index, low dispersion, and low glass transition temperature, which are essential for precision pressing and optical element manufacturing.

Method used

A glass composition with specific oxide content ranges, including B2O3, ZnO, Li2O, Y2O3, and rare earth oxides, tailored to achieve a refractive index of 1.750 to 1.790 and Abbe number of 47.5 to 50.5, with a glass transition temperature below 640°C, optimized for precision press molding.

Benefits of technology

The solution provides optical glasses with enhanced properties for precision pressing, reducing surface defects and improving mold stability, while maintaining high refractive index and low dispersion.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025009783000025
    Figure 2025009783000025
  • Figure 2025009783000001
    Figure 2025009783000001
  • Figure 2025009783000002
    Figure 2025009783000002
Patent Text Reader

Abstract

To provide an optical glass having a high refractive index and a low dispersibility, and also a low glass-transition temperature.SOLUTION: Provided is an optical glass, where in a glass composition of mass% indication, B2O3 content is 15.00 mass% or more and 33.00 mass% or less, ZnO content is 6.00 mass% or more and 18.00 mass% or less, Li2O content is more than 0.00 mass%, Y2O3 content is 3.00 mass% or more and 23.00 mass% or less, the total content of Ta2O5, Nb2O5, Bi2O3, TiO2 and WO3 (Ta2O5+Nb2O5+Bi2O3+TiO2+WO3) is 0.00 mass% or more and 0.30 mass% or less, the total content RE of La2O3, Gd2O3 and Y2O3 is 43.00 mass% or more and 58.00 mass% or less, a mass ratio (RE / (ZrO2+Ta2O5+Nb2O5+WO3)) of the total content RE to the total content of ZrO2, Ta2O5, Nb2O5 and WO3 is 2.00 or more and 13.00 or less, a mass ratio (RE / ZnO) of the total content RE to the ZnO content is 3.80 or more, a refractive index nd is 1.750 or more and 1.790, and Abbe number νd is 47.5 or more and 50.5 or less.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an optical glass and an optical element. [Background technology]

[0002] In recent years, various optical glasses have been proposed as materials for optical elements (see, for example, Patent Document 1). [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2018-065747 A Summary of the Invention [Problem to be solved by the invention]

[0004] Among optical glasses, optical glasses having a high refractive index and low dispersion are useful as materials for optical elements.

[0005] One of the properties desired for optical glass is a low glass transition temperature Tg. Low Tg glass is preferable because it has excellent suitability for precision pressing, for example.

[0006] An object of one aspect of the present invention is to provide an optical glass that has a high refractive index, low dispersion, and a low glass transition temperature. [Means for solving the problem]

[0007] One aspect of the present invention is In the glass composition expressed in mass%, B2O3 content is 15.00% by mass or more and 33.00% by mass or less, ZnO content is 6.00% by mass or more and 18.00% by mass or less, Li2O content exceeds 0.00% by mass, Y2O3 content is 3.00% by mass or more and 23.00% by mass or less, The total content of Ta2O5, Nb2O5, Bi2O3, TiO2 and WO3 (Ta2O5+Nb2O5+Bi2O3+TiO2+WO3) is 0.00% by mass or more and 0.30% by mass or less, The total content RE of La2O3, Gd2O3 and Y2O3 is 43.00 mass% or more and 58.00 mass% or less, The mass ratio of the total content RE to the total content of ZrO2, Ta2O5, Nb2O5 and WO3 (RE / (ZrO2+Ta2O5+Nb2O5+WO3)) is 2.00 or more and 13.00 or less; The mass ratio (RE / ZnO) of the total content of RE to the ZnO content is 3.80 or more. and an optical glass having a refractive index nd of 1.750 or more and 1.790 or less and an Abbe number νd of 47.5 or more and 50.5 or less; Regarding. Effect of the Invention

[0008] According to one aspect of the present invention, there is provided an optical glass having a high refractive index, low dispersion and a low glass transition temperature. Also, according to another aspect of the present invention, there is provided an optical element made of the optical glass. [Brief description of the drawings]

[0009] [Figure 1] 1 shows a schematic cross-sectional view of a precision press molding device. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] [Optical glass] In the present invention and this specification, the glass composition is expressed as a glass composition based on oxides. Here, "glass composition based on oxides" refers to a glass composition obtained by converting the glass raw materials into oxides that are present in the glass after being completely decomposed during melting. Furthermore, unless otherwise specified, the glass composition is expressed on a mass basis (mass %, mass ratio). The glass composition of the present invention and this specification can be determined by a method such as ICP-AES (Inductively Coupled Plasma-Atomic Emission Spectrometry). For example, quantitative analysis is performed for each element using ICP-AES. The analytical values ​​are then converted into oxide notation. The analytical values ​​obtained by ICP-AES may contain a measurement error of, for example, about ±5% of the analytical value. Therefore, the oxide notation values ​​converted from the analytical values ​​may also contain an error of about ±5%. In the present invention and this specification, the content of a component being 0.00%, or not being contained or not being introduced means that the component is substantially not contained, and the content of the component is at or below the level of impurities. At or below the level of impurities means, for example, less than 0.01%.

[0011] In the present invention and this specification, the refractive index refers to the refractive index nd at the d line of helium (wavelength 587.56 nm).

[0012] In the present invention and this specification, the Abbe number νd is used as a value indicating a property related to dispersion, and is expressed by the following formula. νd=(nd-1) / (nF-nC) In the above formula, nF is the refractive index at the F line of blue hydrogen (wavelength 486.13 nm), and nC is the refractive index at the C line of red hydrogen (656.27 nm).

[0013] The optical glass (sometimes simply referred to as "glass") will be described in more detail below.

[0014] <Glass composition> The Li2O content is more than 0.00%. Li2O is an essential component in the optical glass because it is capable of lowering the glass transition temperature while suppressing a decrease in the refractive index. The Li2O content is preferably 0.025% or more, more preferably 0.050% or more, 0.075% or more, 0.10% or more, 0.15% or more, and 0.20% or more in that order. The upper limit of the LiO content is not particularly limited and can be, for example, 2.30% or less, and is preferably 2.20% or less, and is more preferably 2.10% or less, 2.08% or less, 2.06% or less, 2.04% or less, 2.02% or less, 2.00% or less, 1.98% or less, 1.96% or less, and 1.94% or less, in that order.

[0015] Among the alkali metal oxides Li2O, Na2O, K2O and Cs2O, the Li2O content is as described above. The respective contents of Na2O, K2O and Cs2O can be, for example, 0.00%, 0.00% or more, or more than 0.00%, and can be, for example, 5.00% or less, 4.00% or less, 3.00% or less, 2.00% or less, 1.00% or less, 0.50% or less, 0.40% or less, 0.30% or less, 0.20% or less, or 0.10% or less.

[0016] B2O3 is a glass network former and is a component that contributes to maintaining the thermal stability and meltability of glass. Therefore, the B2O3 content is 15.00% or more, preferably 16.00% or more, and more preferably 17.00% or more, 18.00% or more, 18.50% or more, 19.00% or more, 19.25% or more, 19.50% or more, 19.75% or more, 20.00% or more, 20.25% or more, 20.50% or more, 20.75% or more, 21.00% or more, 20.25% or more, and 21.30% or more in that order. B2O3 is also a component that lowers the refractive index of glass when contained in a large amount in glass. Therefore, the B2O3 content is 33.00% or less, preferably 32.00% or less, and more preferably 31.50% or less, 31.00% or less, 30.75% or less, 30.50% or less, 30.25% or less, 30.00% or less, 29.75% or less, 29.50% or less, 29.25% or less, and 29.00% or less in that order.

[0017] SiO2 is also a glass network former and is a component that contributes to maintaining the thermal stability and meltability of glass. From this point of view, the SiO2 content is preferably more than 0.00%, more preferably 0.20% or more, and further preferably 0.40% or more, 0.60% or more, 0.65% or more, 0.70% or more, 0.75% or more, 0.80% or more, 0.85% or more, 0.90% or more, 0.95% or more, 1.00% or more, 1.05% or more, 1.10% or more, 1.15% or more, 1.20% or more, and 1.23% or more in that order. SiO2 is also a component that lowers the refractive index of glass when contained in a large amount in glass. Therefore, the SiO2 content is preferably 13.00% or less, more preferably 12.00% or less, 11.00% or less, 10.75% or less, 10.50% or less, 10.25% or less, 10.00% or less, 9.80% or less, 9.60% or less, 9.40% or less, 9.20% or less, 9.00% or less, 8.80% or less, 8.60% or less, 8.40% or less, and 8.30% or less in that order.

[0018] P2O5 is also a glass network former and is a component that contributes to maintaining the thermal stability and meltability of the glass. The lower limit of the P2O5 content is not particularly limited, and can be, for example, 0.00%, 0.00% or more, or more than 0.00%. P2O5 is also a component that lowers the refractive index of glass when contained in a large amount in glass, so the P2O5 content is preferably 3.00% or less, more preferably 2.50% or less, and even more preferably 2.00% or less, and even more preferably 1.75% or less, 1.50% or less, 1.40% or less, 1.30% or less, 1.20% or less, 1.20% or less, and 1.15% or less in that order.

[0019] The mass ratio of the Li2O content to the SiO2 content (Li2O / SiO2) is preferably 1.00 or less, more preferably 0.90 or less, and further preferably 0.80 or less, 0.70 or less, 0.68 or less, 0.66 or less, 0.64 or less, 0.62 or less, 0.60 or less, 0.58 or less, 0.56 or less, and 0.54 or less in that order. The lower limit may be more than 0.00, and is preferably 0.01 or more, more preferably 0.02 or more, 0.03 or more, 0.04 or more, 0.05 or more, 0.06 or more, 0.07 or more, 0.08 or more, 0.09 or more, and 0.10 or more in that order. With regard to the mass ratio (Li2O / SiO2), the above lower limit is preferable from the viewpoint of lowering the glass transition temperature, and the above upper limit is preferable from the viewpoint of suppressing an increase in the glass transition temperature and maintaining thermal stability.

[0020] The La2O3 content is preferably 20.00% or more, and more preferably in this order: 21.00% or more, 22.00% or more, 23.00% or more, 24.00% or more, 25.00% or more, 26.00% or more, 27.00% or more, 28.00% or more, 28.50% or more, 29.00% or more, 29.50% or more, 30.00% or more, 30.50% or more, 31.00% or more, 31.50% or more, 32.00% or more, 32.50% or more, and 33.00% or more. The La2O3 content is preferably 50.00% or less, and more preferably 49.00% or less, 48.00% or less, 47.00% or less, 46.00% or less, 45.00% or less, 44.50% or less, 44.00% or less, 43.50% or less, 43.00% or less, 42.50% or less, 42.00% or less, 41.75% or less, and 41.60% or less, in that order.

[0021] The Gd2O3 content may be, for example, 0.00%, 0.00% or more, or more than 0.00%. The upper limit is preferably 7.50% or less, more preferably 6.50% or less, 5.50% or less, 5.00% or less, 4.50% or less, 4.00% or less, 3.50% or less, 3.00% or less, 2.80% or less, 2.60%, and 1.25% or less.

[0022] Y2O3 is a component that can improve the thermal stability when contained in a specified amount in glass. From the viewpoint of improving the thermal stability of the glass, the Y2O3 content is 3.00% or more, preferably 4.00% or more, and more preferably 5.00% or more, 6.00% or more, 6.50% or more, 7.00% or more, 7.50% or more, 8.00% or more, 8.50% or more, 8.75% or more, 9.00% or more, 9.25% or more, and 9.50% or more in that order. Furthermore, from the viewpoint of improving the thermal stability of the glass, the Y2O3 content is 23.00% or less, preferably 22.50% or less, and more preferably 22.00% or less, 21.50% or less, 21.00% or less, 20.50% or less, 20.00% or less, 19.50% or less, 19.00% or less, 18.50% or less, 18.25% or less, 18.00% or less, and 17.75% or less in that order.

[0023] With regard to the rare earth components, La2O3, Gd2O3 and Y2O3 are components that can increase the refractive index while maintaining low dispersion, and from the viewpoint of maintaining or improving the thermal stability of the glass, it is preferable that the content of each rare earth oxide is within the above-mentioned range.

[0024] The total content of La2O3, Gd2O3 and Y2O3 is also expressed as "RE". From the viewpoint of maintaining a high refractive index and low dispersion, RE is 43.00% or more, preferably 43.50% or more, and more preferably 44.00% or more, 44.50% or more, 45.00% or more, 45.50% or more, 46.00% or more, 46.50% or more, 47.00% or more, 47.50% or more, 48.00% or more, 48.50% or more, 49.00% or more, 49.25% or more, 49.50% or more, and 49.75% or more in that order. Moreover, from the viewpoint of maintaining or improving the thermal stability of the glass, RE is 58.00% or less, preferably 57.50% or less, and more preferably 57.00% or less, 56.50% or less, 56.00% or less, 55.50% or less, 55.18% or less, 55.00% or less, 54.75% or less, 54.50% or less, 54.25% or less, 54.00% or less, and 53.75% or less in that order.

[0025] The ZnO content is 6.00% or more, preferably 6.50% or more, more preferably 7.00% or more, 7.25% or more, 7.50% or more, 7.75% or more, 8.00% or more, 8.20% or more, 8.40% or more, 8.60% or more, and 8.75% or more in that order. The upper limit is 18.00% or less, preferably 17.50% or less, more preferably 17.00% or less, 16.50% or less, 16.00% or less, 15.50% or less, 15.00% or less, 14.50% or less, 14.00% or less, 13.75% or less, 13.50% or less, and 13.25% or less in that order. ZnO is a component that reduces the glass transition temperature and improves melting properties while suppressing the decrease in refractive index. On the other hand, if a large amount of ZnO is contained in glass, the liquidus temperature becomes high and the thermal stability of the glass decreases. From these viewpoints, the ZnO content is preferably within the above range.

[0026] From the viewpoint of further lowering the glass transition temperature, the total content of Li2O and ZnO (Li2O+ZnO) is preferably 7.00% or more, more preferably 8.00% or more, 8.50% or more, 9.00% or more, 9.25% or more, and 9.50% or more in that order. From the viewpoint of maintaining or improving the thermal stability of the glass, the upper limit is preferably 19.00% or less, more preferably 18.50% or less, 18.00% or less, 17.50% or less, 17.00% or less, 16.50% or less, 16.25% or less, 16.00% or less, 15.75% or less, 15.50% or less, and 15.20% or less in that order.

[0027] The ZrO2 content can be 0.00%, 0.00% or more, or more than 0.00%, and is preferably 3.00% or more, more preferably 3.50% or more, 4.00% or more, 4.25% or more, 4.50% or more, 4.64% or more, 4.75% or more, 5.00% or more, and 5.10% or more in that order. The upper limit is preferably 10.00% or less, more preferably 9.50% or less, 9.00% or less, 8.75% or less, 8.50% or less, 8.25% or less, 8.00% or less, and 7.90% or less. More preferably 7.80% or less, 7.70% or less, 7.60% or less, 7.50% or less, 7.40% or less, and 7.30% or less in that order. The above optical glass preferably contains ZrO2 because the introduction of ZrO2 into the glass improves the thermal stability of the glass without decreasing the refractive index of the glass. On the other hand, an increase in the ZrO2 content causes an increase in the melting temperature. From these viewpoints, the ZrO2 content is preferably within the above range.

[0028] The total content of Ta2O5, Nb2O5, Bi2O3, TiO2 and WO3 (Ta2O5+Nb2O5+Bi2O3+TiO2+WO3) is 0.00% or more, and can be 0.00%. The upper limit is 0.30% or less, preferably 0.25% or less, more preferably 0.20% or less, 0.15% or less, 0.10% or less, 0.08% or less, 0.06% or less, 0.04% or less, 0.02% or less, and 0.00% in that order. The above upper limit of the total content (Ta2O5+Nb2O5+Bi2O3+TiO2+WO3) is preferable from the viewpoint of maintaining the thermal stability of the glass. Furthermore, Ta2O5, Nb2O5, Bi2O3, TiO2 and WO3 tend to react with the molding surface of the mold during press molding, deteriorating the surface quality of the glass, and may also intensify the coloring of the glass. Therefore, it is most preferable that the optical glass does not contain Ta2O5, Nb2O5, Bi2O3, TiO2 and WO3, that is, the total content (Ta2O5+Nb2O5+Bi2O3+TiO2+WO3) is 0.00%. The respective contents of Ta2O5, Nb2O5, Bi2O3, TiO2 and WO3 are preferably 0.30% or less, more preferably 0.25% or less, further preferably 0.20% or less, 0.15% or less, 0.10% or less, 0.08% or less, 0.06% or less, 0.04% or less, and 0.02% or less, in that order, and are most preferably 0.00%.

[0029] The mass ratio RE of the total content of La2O3, Gd2O3 and Y2O3 to the total content of ZrO2, Ta2O5, Nb2O5 and WO3 (RE / (ZrO2+Ta2O5+Nb2O5+WO3)) is 2.00 or more, preferably 3.00 or more, and more preferably 4.00 or more, 4.20 or more, 4.40 or more, 4.60 or more, 4.80 or more, 5.00 or more, 5.20 or more, 5.40 or more, 5.60 or more, 5.80 or more, 6.00 or more, 6.20 or more, 6.40 or more, 6.60 or more, and 6.80 or more in that order. The upper limit is 13.00 or less, preferably 12.00 or less, and more preferably 11.80 or less, 11.60 or less, 11.40 or less, 11.20 or less, 10.00 or less, 10.90 or less, 10.80 or less, 10.70 or less, 10.60 or less, and 10.50 or less, in that order. With respect to the mass ratio (RE / (ZrO2+Ta2O5+Nb2O5+WO3)), the above lower limit is preferable from the viewpoint of maintaining the low dispersion of the glass, and the above upper limit is preferable from the viewpoint of maintaining the thermal stability.

[0030] The mass ratio (RE / ZnO) of the total content RE of La2O3, Gd2O3 and Y2O3 to the ZnO content is 3.80 or more, preferably 3.81 or more, and more preferably 3.82 or more. There is no particular upper limit, and the upper limit is preferably 9.00 or less, more preferably 8.50 or less, 8.00 or less, 7.50 or less, 7.00 or less, 6.80 or less, 6.60 or less, 6.40 or less, 6.20 or less, 6.00 or less, and 5.95 or less in that order. With respect to the mass ratio (RE / ZnO), the above lower limit is preferred from the viewpoint of maintaining low dispersion of the glass, and the above upper limit is preferred from the viewpoint of maintaining a low glass transition temperature.

[0031] The optical glass may or may not contain one or more alkaline earth metal oxides. In the optical glass, the content of each of MgO, CaO, SrO, and BaO may be, for example, 0.00%, 0.00% or more, more than 0.00%, 0.01% or more, 0.10% or more, or 0.50% or more, and may be, for example, 3.00% or less, 2.00% or less, or 1.00% or less.

[0032] Sb2O3 is a component that can be added as a clarifier. The smaller the amount of Sb2O3 added, the more preferable it is from the viewpoint of suppressing damage to the molding surface of the press mold during precision press molding and from the viewpoint of suppressing coloring of the glass. The Sb2O3 content is preferably 0.00% or more, 0.01% or more, and 0.02% or more in the order of Sb2O3 content expressed as an exclusive percentage (Sb2O3 content when the total mass of glass components other than Sb2O3 is 100% by mass) in the glass composition expressed in mass%, and is also preferably 1.00% or less, 0.90% or less, 0.80% or less, 0.70% or less, 0.60% or less, 0.50% or less, 0.40% or less, 0.30% or less, 0.20% or less, and 0.10% or less in the order of Sb2O3 content expressed as an exclusive percentage (Sb2O3 content when the total mass of glass components other than Sb2O3 is 100% by mass).

[0033] SnO2 can also be added as a clarifier, but if it is added in an amount exceeding 1.00% by weight, the glass will become colored, and when the glass is heated and softened and reshaped by press molding or the like, Sn will become the starting point for crystal nucleation, causing a tendency for devitrification. Therefore, the amount of SnO2 added is preferably 0.00% or more and 1.00% or less by weight, more preferably 0.00% or more and 0.50% or less, and it is particularly preferable to not add any SnO2. The SnO2 content by weight refers to the SnO2 content expressed in mass% when the total content of glass components other than SnO2 is taken as 100 mass%.

[0034] The optical glass can be produced without containing components such as Lu and Hf. Since Lu and Hf are expensive components, it is preferable to suppress the content of Lu2O3 and HfO2 to 0.00% or more and 2.00% or less, more preferably to suppress the content of 0.00% or more and 1.00% or less, even more preferably to suppress the content of 0.00% or more and 0.80% or less, and even more preferably to suppress the content of 0.00% or more and 0.10% or less, and it is particularly preferable not to introduce Lu2O3 and not to introduce HfO2. Moreover, in consideration of the environmental impact, it is preferable not to incorporate Pb, and it is also preferable not to incorporate As, U, Th, Te, or Cd. Furthermore, from the viewpoint of taking advantage of the excellent light transmittance of glass, it is preferable not to incorporate substances that cause coloring, such as Cu, Cr, V, Fe, Ni, and Co.

[0035] <Glass properties> (glass transition temperature Tg) The optical glass can have a low glass transition temperature Tg by having the above glass composition. Low Tg glass is preferable, for example, in producing an optical element without scratches, cloudiness, or breakage on the surface by precision press molding. Low Tg glass is also preferable from the viewpoint of suppressing deterioration of the release film and suppressing wear of the press molding die in precision press molding. The Tg of the optical glass is preferably less than 640°C, and is more preferably 638°C or less, 636°C or less, 634°C or less, 632°C or less, 630°C or less, 628°C or less, 626°C or less, 624°C or less, 622°C or less, and 620°C or less in that order. The lower limit of Tg is not particularly limited, and can be, for example, 530°C or more, 540°C or more, 550°C or more, 555°C or more, 560°C or more, 565°C or more, or 570°C or more. The glass transition temperature Tg is determined by the method described below.

[0036] (Refractive index nd) High refractive index glass is useful as a material for optical elements. The refractive index nd of the optical glass is 1.7500 or more, preferably 1.7530 or more, more preferably 1.7550 or more, 1.7570 or more, 1.7590 or more, 1.7610 or more, 1.7630 or more, and 1.7632 or more in this order. The upper limit is 1.7900 or less, preferably 1.7910 or less, more preferably 1.7890 or less, 1.7870 or less, 1.7850 or less, 1.7830 or less, 1.7810 or less, 1.7790 or less, 1.7770 or less, and 1.7760 or less in this order.

[0037] (Abbe number νd) Glasses exhibiting low dispersion are useful as materials for optical elements. The Abbe number νd of the optical glass is 47.50 or more, preferably 48.20 or more, more preferably 48.30 or more, 48.35 or more, 48.40 or more, 48.45 or more, 48.50 or more, 48.55 or more, 48.60 or more, 48.65 or more, and 48.70 or more in this order. The upper limit is 50.50 or less, preferably 50.20 or less, more preferably 50.15 or less, 50.10 or less, 50.05 or less, 50.00 or less, 49.95 or less, 49.90 or less, and 49.86 or less in this order. When glass is considered as a material for optical elements, increasing the refractive index of glass corresponds to expanding the degree of freedom of glass. Increasing the refractive index is preferable from the viewpoint of expanding the degree of freedom. On the other hand, if the refractive index is increased while maintaining the dispersion, the glass stability may tend to decrease. From these viewpoints, the Abbe number νd is preferably in the above-mentioned range.

[0038] (Coloring degree λ5, λ 80 ) The light transmittance of the glass, specifically, the suppression of the shift of the light absorption edge on the short wavelength side to longer wavelengths, is the coloring degree λ5 and λ 80 The coloring degree λ5 represents the wavelength at which the spectral transmittance (including surface reflection loss) of a 10 mm thick glass is 5% from the ultraviolet region to the visible region. λ 80 represents the wavelength at which the spectral transmittance measured by the method described for λ5 is 80%. 80 is a value measured in the wavelength range of 250 to 700 nm. The spectral transmittance T (%) of glass in the present invention and this specification is calculated by dividing the intensity of light incident perpendicularly on one of two optically polished parallel planes of a glass sample by the intensity of light I in The intensity of the light that passes through the glass sample and exits from the other side is I out When T(%)=I out / I in ×100 It is expressed as: Coloring degree λ5 and λ80 According to this, the absorption edge on the short wavelength side of the spectral transmittance can be quantitatively evaluated. When bonding lenses together with an ultraviolet-curing adhesive to produce a cemented lens, the adhesive is cured by irradiating it with ultraviolet light through an optical element. From the viewpoint of efficiently curing the ultraviolet-curing adhesive, it is preferable that the absorption edge on the short wavelength side of the spectral transmittance is in a short wavelength range. As an index for quantitatively evaluating the absorption edge on the short wavelength side, the coloring degree λ5 and λ 80 One or more of the following may be used. The optical glass preferably exhibits λ5 of 320 nm or less. λ5 is more preferably 310 nm or less, 300 nm or less, and 290 nm or less, in that order. The shorter the wavelength of λ5, the more preferable it is, and there is no particular lower limit. The optical glass preferably has a λ of 510 nm or less. 80 It can be shown that λ 80 is more preferably 400 nm or less, 390 nm or less, 380 nm or less, and 377 nm or less, in that order. 80 The shorter the wavelength, the more preferable it is, and the lower limit is not particularly limited.

[0039] <Glass manufacturing method> The optical glass can be obtained by weighing, preparing and thoroughly mixing raw materials such as oxides, carbonates, sulfates, nitrates and hydroxides so as to obtain the desired glass composition, heating, melting, degassing and stirring the mixture in a melting vessel such as a platinum vessel to produce a homogeneous, bubble-free molten glass, and then molding the glass. Specifically, the glass can be produced by using a known melting method. As mentioned above, an increase in the ZrO2 content causes an increase in the melting temperature. On the other hand, when a platinum container is used as a melting container, if the melting temperature becomes high, Pt ions are eluted from the platinum container and the transmittance deteriorates, so the above coloring degrees λ5 and λ 80 Therefore, a low melting temperature (for example, 1000°C or higher and 1300°C or lower) increases the coloring degree λ5 and λ 80From this point of view, it is preferable that the content of ZrO2 is within the above-mentioned range.

[0040] [Glass material for press molding, its manufacturing method, and manufacturing method of glass molded body] According to one aspect of the present invention, there are provided a glass material for press molding made of the above-mentioned optical glass, a glass molded article made of the above-mentioned optical glass, and methods for producing them. The glass material for press molding means glass lump that is heated and subjected to press molding. Examples of glass materials for press molding include glass blocks having a mass equivalent to the mass of press-molded products such as precision press molding preforms and glass materials (glass gobs for press molding) for press molding optical element blanks. The glass material for press molding can be produced, for example, through a process of processing a glass molded body. The glass molded body can be produced by heating and melting a glass raw material as described above, and molding the resulting molten glass. Examples of the processing method for the glass molded body include cutting, grinding, polishing, etc. Also, an example of producing a preform for precision press molding will be described later.

[0041] [Optical element blank and its manufacturing method] According to one aspect of the present invention, an optical element blank made of the above optical glass can be provided. The optical element blank is a glass molded body having a shape similar to that of the optical element to be manufactured. The optical element blank can be produced by a method of molding glass into a shape obtained by adding a processing allowance to be removed by processing to the shape of the optical element to be manufactured. For example, the optical element blank can be produced by a method of heating and softening a glass material for press molding and press molding it (reheat press method), or a method of supplying a molten glass lump to a press mold by a known method and press molding it (direct press method).

[0042] [Optical elements and their manufacturing methods] According to one aspect of the present invention, an optical element made of the above optical glass can be provided. Examples of the types of optical elements include lenses such as spherical lenses and aspherical lenses, prisms, and diffraction gratings. Examples of the lens shapes include biconvex lenses, plano-convex lenses, biconcave lenses, plano-concave lenses, convex meniscus lenses, and concave meniscus lenses.

[0043] As one embodiment of the method for producing an optical element, a method for producing an optical element by heating a preform for precision press molding and performing precision press molding can be mentioned. A known press mold can be used for precision press molding, and a known molding method can be applied. The method for producing an optical element by precision press molding is suitable for producing aspherical lenses, microlenses, diffraction gratings, etc.

[0044] The surface of the precision press molding preform can be coated with a mold release film to prevent the glass from fusing with the press mold surface during precision press molding while allowing the glass to spread well along the molding surface. Such mold release films are known. A precision press molding preform made of low Tg glass is preferable from the viewpoint of suppressing deterioration of the mold release film. An example of the mold release film is a carbon-containing film. The carbon-containing film can be, for example, a film mainly composed of carbon (when the element content in the film is expressed in atomic %, the carbon content is higher than the content of other elements). The carbon-containing film can be formed by known methods such as vacuum deposition, sputtering, and ion plating using a carbon raw material, or known methods such as pyrolysis using a material gas such as hydrocarbon.

[0045] A schematic cross-sectional view of a precision press molding apparatus is shown in Figure 1. Precision press molding can be carried out, for example, as follows. After placing a precision press molding preform (hereinafter simply referred to as "preform") 4 between a lower die 2 and an upper die 1 that constitute a press molding die, a nitrogen atmosphere is created inside the quartz tube 11, and electricity is passed through a heater (not shown) to heat the inside of the quartz tube 11. The temperature inside the press molding die is raised to, for example, 10 6 ~1010 The temperature is set to a temperature at which the viscosity of the glass is 10 dPa·s, and while maintaining the same temperature, the push rod 13 is lowered to push the upper die 1 and press the preform set in the mold. After pressing, the pressure of the press is released, and while the pressed glass molded product is still in contact with the lower die 2 and the upper die 1, the viscosity of the glass is adjusted to, for example, 10 12 The glass molded product is slowly cooled to a temperature of at least dPa·s, and then rapidly cooled to room temperature, and removed from the mold. In this manner, an optical element can be obtained. In Fig. 1, a holding member 10 holds the lower die 2 and the body die 3, and a support rod 9 supports the upper die 1, lower die 2, body die 3, and holding member 10, while receiving the pressing pressure from a pressing rod 13. A thermocouple 14 is inserted inside the lower die 2 to monitor the temperature inside the press mold.

[0046] Another embodiment of the method for producing an optical element is a method for producing an optical element by machining an optical element blank. Examples of the machining include cutting, milling, rough grinding, fine grinding, polishing, etc. This manufacturing method is suitable for producing spherical lenses, prisms, etc. EXAMPLES

[0047] The present invention will be described in more detail below with reference to examples, although the present invention is not limited to the embodiments shown in the examples.

[0048] [Examples No. 1 to No. 154] To obtain the glass composition shown in the table below, the corresponding phosphates, fluorides, nitrates, sulfates, carbonates, hydroxides, oxides, boric acid, etc. were used as raw materials for introducing each component, and the raw materials were weighed and thoroughly mixed to obtain a blended raw material. In the table below, the Sb2O3 content is shown as an exclusive percentage. The mixed raw materials were placed in a platinum crucible and heated and melted for 120 minutes in a furnace set at 1000-1300° C. The molten glass was stirred to homogenize it, then poured into a preheated mold and allowed to cool to near the glass transition temperature, and immediately placed in an annealing furnace, where it was held at about the glass transition temperature for about 30 minutes, then slowly cooled at a rate of -30° C. / hour for 4 hours, and then allowed to cool to room temperature in the furnace to obtain the optical glasses No. 1 to No. 154 shown in the table below.

[0049] <Physical property measurements> The physical properties of each optical glass shown in the following table were measured by the following methods.

[0050] (1) Refractive index nd, Abbe number νd The refractive index nd and Abbe number vd of each optical glass were measured by the refractive index measurement method specified by the Japan Optical Glass Industry Association.

[0051] (2) Glass transition temperature Tg The glass was thoroughly crushed in a mortar and used as a sample. A platinum cell was used as a sample container, and the glass transition temperature Tg was measured at a heating rate of 10°C / min using a differential scanning calorimeter (DSC3300SA) manufactured by NETZSCH JAPAN.

[0052] (3) Coloring degree λ5, λ 80 A glass sample with a thickness of 10±0.1 mm and two optically polished flat surfaces facing each other was used to measure the spectral transmittance T (%) using a spectrophotometer. The wavelength (nm) at which T is 5% is defined as λ5, and the wavelength (nm) at which T is 80% is defined as λ6. 80 It was decided.

[0053] The results are shown in the table below.

[0054] [Table 1-1]

[0055] [Table 1-2]

[0056]

Table 1-3

[0057]

Table 1-4

[0058]

Table 1-5

[0059]

Table 1-6

[0060]

Table 1-7

[0061]

Table 1-8

[0062]

Table 2-1

[0063]

Table 2-2

[0064]

Table 2-3

[0065]

Table 2-4

[0066]

Table 2-5

[0067]

Table 2-6

[0068]

Table 2-7

[0069]

Table 2-8

[0070]

Table 3-1

[0071]

Table 3-2

[0072]

Table 3-3

[0073]

Table 3-4

[0074]

Table 3-5

[0075]

Table 3-6

[0076] [Table 3-7]

[0077] [Table 3-8]

[0078] <Production of optical elements by precision press molding> For each of the above examples, the corresponding nitrates, sulfates, carbonates, hydroxides, oxides, boric acid, etc. were used as raw materials for introducing each component so as to obtain the glass composition shown in the above table, and the raw materials were weighed and thoroughly mixed to obtain a blended raw material. One example of preform production (Production Example 1) will be described. The mixed raw materials were placed in a platinum crucible, and heated and melted. The clarified and homogenized molten glass was allowed to flow at a constant rate from a platinum alloy pipe, the temperature of which was adjusted to a temperature range that allowed stable flow without devitrification of the glass, and separated into molten glass lumps of the desired preform mass by a dropping or drop cutting method. The separated molten glass lumps were received in a mold with a gas nozzle at the bottom, and gas was ejected from the gas nozzle to float the glass lumps, forming a preform for precision press molding. A flattened spherical preform was obtained by adjusting and setting the separation interval of the molten glass lumps. Another example of preform production (production example 2) is a method in which a homogeneous molten glass obtained by melting a blend of raw materials is poured into a mold and molded, distortion in the resulting molded body is removed by annealing, the molded body is cut or fractured to divide it into pieces of specified dimensions and shapes to produce a plurality of glass pieces, and the glass pieces are polished to smooth their surfaces and formed into a preform made of glass of a specified mass. For each of the above-mentioned Examples, a preform for precision press molding was produced according to Production Example 2. The melting temperature when melting the blended raw materials was set to 1000°C or more and 1300°C or less.

[0079] For each of the above examples, the surface of the preform produced is coated with a carbon-containing film, and the preform is introduced into a press mold including upper and lower dies and a body die made of SiC with a carbon-containing release film on the molding surface, and the mold and the preform are heated together in a nitrogen atmosphere to soften the preform, and precision press molding is performed to produce various lenses (aspheric convex meniscus lens, aspheric concave meniscus lens, aspheric biconvex lens, aspheric biconcave lens) made of the above various glasses. When the various lenses produced in this way were observed, no scratches, cloudiness or damage were found on the lens surface.

[0080] Finally, the above-mentioned aspects will be summarized.

[0081] [1] In the glass composition expressed in mass%, B2O3 content is 15.00% by mass or more and 33.00% by mass or less, ZnO content is 6.00% by mass or more and 18.00% by mass or less, Li2O content exceeds 0.00% by mass, Y2O3 content is 3.00% by mass or more and 23.00% by mass or less, The total content of Ta2O5+Nb2O5+Bi2O3+TiO2+WO3 (Ta2O5+Nb2O5+Bi2O3+TiO2+WO3) is 0.00% by mass or more and 0.30% by mass or less, The total content RE of La2O3, Gd2O3 and Y2O3 is 43.00 mass% or more and 58.00 mass% or less, The mass ratio of the total content RE to the total content of ZrO2, Ta2O5, Nb2O5 and WO3 (RE / (ZrO2+Ta2O5+Nb2O5+WO3)) is 2.00 or more and 13.00 or less; The mass ratio (RE / ZnO) of the total content RE to the ZnO content is 3.80 or more. and An optical glass having a refractive index nd of 1.750 or more and 1.790 or less, and an Abbe number νd of 47.5 or more and 50.5 or less. [2] The optical glass according to [1], in which the mass ratio of Li2O to the SiO2 content (Li2O / SiO2) is greater than 0 and less than or equal to 1.00. [3] The optical glass according to [1] or [2], wherein the total content of LiO2 and ZnO (LiO2 + ZnO) is 7.00 mass% or more and 19.00 mass% or less. [4] The optical glass according to any one of [1] to [3], which has a glass transition temperature Tg of lower than 640° C. [5] Coloring degree λ 80 The optical glass according to any one of [1] to [4], wherein the optical transmittance is 510 nm or less. [6] The mass ratio of Li2O to SiO2 content (Li2O / SiO2) is greater than 0 and less than or equal to 1.00; The total content of LiO2 and ZnO (LiO2 + ZnO) is 7.00 mass% or more and 19.00 mass% or less, The glass transition temperature Tg is less than 640°C, and Coloring degree λ 80 The optical glass according to any one of [1] to [5], wherein the optical transmittance is 510 nm or less. [7] An optical element comprising the optical glass according to any one of [1] to [6].

[0082] The embodiments disclosed herein should be considered to be illustrative and not restrictive in all respects. The scope of the present invention is defined by the claims, not the above description, and is intended to include all modifications within the meaning and scope of the claims. For example, by subjecting the above-mentioned exemplary glass compositions to compositional adjustments as described in the specification, an optical glass according to one aspect of the present invention can be obtained. Furthermore, it is of course possible to arbitrarily combine two or more of the items described in the specification as examples or preferred ranges.

Claims

1. In the glass composition expressed in mass%, B 2 O 3 The content is 15.00 mass% or more and 33.00 mass% or less, ZnO content is 6.00% by mass or more and 18.00% by mass or less, Li 2 O content is more than 0.00 mass%, Y 2 O 3 The content is 3.00 mass% or more and 23.00 mass% or less, T 2 O 5 , Nb 2 O 5 , Bi 2 O 3 , TiO 2 and W.O. 3 The total content (Ta 2 O 5 +Nb 2 O 5 +Bi 2 O 3 + TiO 2 +W.O. 3 ) is 0.00% by mass or more and 0.30% by mass or less, La 2 O 3 , Gd 2 O 3 and Y 2 O 3 The total content RE is 43.00 mass% or more and 58.00 mass% or less, ZrO 2 , Ta 2 O 5 , Nb 2 O 5 and W.O. 3 The mass ratio of the total content RE to the total content (RE / (ZrO 2 +Ta 2 O 5 +Nb 2 O 5 +W.O. 3 ) is 2.00 or more and 13.00 or less, The mass ratio (RE / ZnO) of the total content RE to the ZnO content is 3.80 or more. and An optical glass having a refractive index nd of 1.7500 or more and 1.7900 or less, and an Abbe number vd of 47.50 or more and 50.50 or less.

2. SiO 2 Li content 2 Mass ratio of O content (Li 2 O / SiO 2 2. The optical glass according to claim 1 , wherein n is greater than 0 and is 1.00 or less.

3. LiO 2 and ZnO total content (LiO 2 2. The optical glass according to claim 1, wherein the content of ZnO is from 7.00% to 19.00% by mass.

4. 2. The optical glass according to claim 1, having a glass transition temperature Tg of less than 640°C.

5. Coloring degree λ 80 The optical glass according to claim 1 , wherein the optical transmittance is 510 nm or less.

6. SiO 2 Li content 2 Mass ratio of O content (Li 2 O / SiO 2 ) is greater than 0 and less than or equal to 1.00; LiO 2 and ZnO total content (LiO 2 +ZnO) is 7.00 mass% or more and 19.00 mass% or less, The glass transition temperature Tg is less than 640° C., and Coloring degree λ 80 The optical glass according to claim 1 , wherein the optical transmittance is 510 nm or less.

7. An optical element comprising the optical glass according to any one of claims 1 to 6.

Citation Information

Patent Citations

  • Optical glass and optical element

    CN105645766A

  • Optical glass and optical element produced from it

    JP2004231501A

  • Optical glass, preform, and optical element

    JP2015044724A

  • Optical glass and optical elements

    JP2019511445A

  • Glass, glass blank for press-forming, optical element blank, and optical element

    JP2018065747A